Pd / (HfNb series) C / TaZr composite film and preparation method thereof

By introducing a (HfNb-type) C film layer on the surface of the TaZr film to form a Pd/(HfNb-type) C/TaZr composite film, the problem of degradation of hydrogen permeability due to interfacial interdiffusion of existing hydrogen separation membrane materials is solved, and the stability and service life of the composite film are improved.

CN119530739AActive Publication Date: 2025-02-28NORTHWEST INSTITUTE FOR NONFERROUS METAL RESEARCH
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411718024.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-28
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

The existing hydrogen separation membrane materials have deteriorated and failed due to interfacial interdiffusion, which limits their widespread use in industrial applications.

Method used

Using a Pd/(HfNb-based) C/TaZr composite film, the (HfNb-based) C film layer was introduced on the surface of the TaZr film to inhibit the interdiffusion between the Pd particles and the TaZr film matrix, and the hydrogen permeability of the composite film was maintained stable.

Benefits of technology

It effectively improves the stability of the composite membrane during hydrogen permeation, extends its service life, and avoids the decline in hydrogen permeation performance caused by oxidation.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a Pd / (HfNb series) C / TaZr composite film, Pd is loaded on the surface of the (HfNb series) C / TaZr composite film in the form of nanoparticles, the Pd nanoparticles are 5-50 nm, (HfNb series) C is obtained by carbonizing a high-entropy film formed by mixing HfNb with one or more than two of Ti, Ta and Zr, the thickness of the (HfNb series) C is 0.05-0.15 [mu] m, and the mass percentage content of Zr in TaZr is 0.5-8%; the preparation method of the composite film comprises the following steps: 1, smelting; 2, processing a TaZr foil sheet; 3, preparing a film layer on the surface of the TaZr foil and carbonizing; 4, Pd nano particles are deposited; and 5, annealing. By introducing the (HfNb system) C film layer on the surface of the TaZr film, mutual diffusion at the interface of the composite film layer is inhibited, degradation and failure of the hydrogen permeation performance of the composite film are avoided, the stability of the composite film in the hydrogen permeation process is improved, and the method is suitable for the field of hydrogen purification.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hydrogen separation membrane materials and metal composite membranes, and specifically relates to a Pd / (HfNb series) C / TaZr composite membrane and a preparation method thereof. Background Art

[0002] As a flexible secondary energy source, hydrogen energy is currently mainly used in combination with fuel cells, which is of great significance for achieving energy conservation and emission reduction. Due to the unique physical and chemical properties of hydrogen, it has a safety price difference. Therefore, in actual application, it is a convenient and safe way to store and transport hydrogen with the help of hydrogen storage carriers. Methanol, as a liquid, is easy to store and transport and is a relatively ideal hydrogen storage carrier. Combining the methanol steam reforming hydrogen production reaction with a membrane purification reactor to achieve integrated reaction-separation hydrogen production can be applied to the scenario of miniaturized in-situ hydrogen production.

[0003] Palladium or palladium alloy membranes are the most commonly used hydrogen separation membranes. The catalytic dissociation ability of metal palladium on hydrogen molecules and the rapid permeation characteristics of interstitial hydrogen atoms in palladium at high temperatures are used to separate or enrich hydrogen from other impurity gases. However, the high price of metal palladium limits its widespread application in industry.

[0004] Tantalum (Ta), niobium (Nb), vanadium (V) and other VB group refractory transition metals have a hydrogen permeation coefficient 1 to 2 orders of magnitude higher than palladium at appropriate temperatures, good mechanical strength and easy to be made into various shapes, and the cost is only a few tenths of palladium. They are very promising hydrogen separation membrane materials. However, VB group metals lack catalytic dissociation activity for hydrogen molecules and are prone to form a dense oxide film on the surface that has a blocking effect on hydrogen atom penetration, resulting in a low actual hydrogen permeation rate, which greatly limits their application as hydrogen permeation separation membrane materials.

[0005] The conventional solution is to plate a layer of palladium film on the surface of the VB group metal. However, when used at high temperatures, due to mutual diffusion at the interface, after a certain period of hydrogen permeation, a compound of palladium and VB group metal is formed at the interface of the composite membrane, causing the hydrogen permeation performance of the composite membrane to deteriorate or even fail. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a Pd / (HfNb series)C / TaZr composite film in view of the above-mentioned deficiencies in the prior art. The composite film introduces a (HfNb series)C film layer on the surface of the TaZr film, effectively inhibits the mutual diffusion between the Pb particles and the TaZr film matrix at the interface of the composite film layer, avoids the degradation and failure of the hydrogen permeation performance of the composite film, improves the stability of the composite film during the hydrogen permeation process, and solves the problem that the existing composite film affects the hydrogen permeation performance due to interface mutual diffusion.

[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is: a Pd / (HfNb series)C / TaZr composite film, characterized in that Pd is loaded on the surface of the (HfNb series)C / TaZr composite film in the form of nanoparticles, wherein the size of the Pd nanoparticles is 5nm~50nm, and the (HfNb series)C is obtained by carbonizing a high entropy film mixed with HfNb and one or more of Ti, Ta, and Zr, with a thickness of 0.05μm~0.15μm, and the mass percentage of Zr in TaZr is 0.5%~8%.

[0008] The above-mentioned Pd / (HfNb series)C / TaZr composite film is characterized in that the metal elements of HfNb in the (HfNb series)C are in an equiatomic ratio, and the (HfNb series)C is obtained by carbonizing a high-entropy film mixed with HfNb and one or more of Ti, Ta, and Zr, wherein the metal atomic ratio of Hf to any one of Ti, Ta, and Zr is 1:4 to 4:1.

[0009] The above-mentioned Pd / (HfNb system) C / TaZr composite film is characterized in that the mass percentage of Zr in the TaZr is 0.5% to 3%.

[0010] At the same time, the present invention also discloses a method for preparing the above-mentioned Pd / (HfNb system) C / TaZr composite film, characterized in that the method comprises the following steps:

[0011] Step 1: Evenly mix tantalum beans and zirconium sponge, and then smelt them in an arc melting furnace to obtain TaZr alloy;

[0012] Step 2: Using a rolling process, the TaZr alloy obtained in step 1 is processed into a TaZr foil, which is then processed to a target size and polished for standby use;

[0013] Step 3: using a magnetron sputtering process, a HfNb film layer is prepared on the surface of the TaZr foil to be used in step 2, and then carbonized to form a (HfNb) C film layer to obtain a (HfNb) C / TaZr composite film;

[0014] Step 4: using a magnetron sputtering process, depositing Pd nanoparticles on the surface of the (HfNb-based) C / TaZr composite film obtained in step 3 to obtain a (HfNb-based) C / TaZr composite film loaded with Pd nanoparticles;

[0015] Step 5: annealing the (HfNb-based) C / TaZr composite film loaded with Pd nanoparticles obtained in step 4 under the protection of a mixed atmosphere of argon and hydrogen to obtain a Pd / (HfNb-based) C / TaZr composite film.

[0016] The above-mentioned preparation method is characterized in that the thickness of the TaZr foil in step 2 is 0.1 mm to 0.3 mm.

[0017] The above-mentioned preparation method is characterized in that the process of carbonizing to form the (HfNb series) C film layer in step three is: the carbonization gas is a mixed gas of argon and methane, and the volume proportion of methane in the mixed gas is 15% to 40%, the carbonization power is 150W to 300W, and the time is 30min to 50min.

[0018] The above-mentioned preparation method is characterized in that the time for depositing Pd nanoparticles in step 4 is 10 minutes to 20 minutes.

[0019] The above-mentioned preparation method is characterized in that the argon flow rate in the mixed atmosphere of argon and hydrogen in step 5 is 0.15m 3 / h~0.4m 3 / h, the flow ratio of argon to hydrogen is 3:1 to 1:1.

[0020] The above-mentioned preparation method is characterized in that the temperature of the annealing treatment in step 5 is 500°C±10°C.

[0021] Compared with the prior art, the present invention has the following advantages:

[0022] 1. The present invention introduces a (HfNb-based) C film layer on the surface of the TaZr film, thereby effectively inhibiting the mutual diffusion between the Pb particles and the TaZr film matrix at the interface of the composite film layer, maintaining the stability of the hydrogen permeation flux of the composite membrane, avoiding the degradation and failure of the hydrogen permeation performance of the composite membrane, improving the stability of the composite membrane during the hydrogen permeation process, and extending the service life of the composite membrane.

[0023] 2. The present invention introduces a (HfNb-based) C film layer on the surface of the TaZr film and utilizes the protective effect of the (HfNb-based) C film layer to effectively inhibit the oxidation of the TaZr surface by oxygen, thereby preventing the TaZr film matrix from being oxidized during service and losing its hydrogen permeation ability, thereby further improving the stability of the hydrogen permeation performance of the composite film.

[0024] 3. The (HfNb-based) C film layer introduced on the surface of the TaZr film in the present invention increases the amount of hydrogen adsorbed in the composite film and intercepts the remaining gases, effectively reducing the gas polarization effect on the surface of the composite film and improving the hydrogen permeation stability of the composite film.

[0025] 4. The composite membrane preparation process of the present invention is simple, short, easy to operate, environmentally friendly, low cost, suitable for large-scale production, and the composite membrane can be used as a metal membrane in the field of hydrogen purification.

[0026] The technical solution of the present invention is further described in detail below through embodiments. DETAILED DESCRIPTION

[0027] Example 1

[0028] In the Pd / (TaHfNbZr)C / TaZr composite film of this embodiment, Pd is loaded on the surface of the (TaHfNbZr)C / TaZr composite film in the form of nanoparticles, wherein the size of the Pd nanoparticles is 5nm to 30nm, (TaHfNbZr)C is obtained by carbonizing a high entropy film mixed with HfNb, Ta and Zr, and has a thickness of 0.05μm, the metal elements of HfNb are in an equiatomic ratio, Ta and Zr are in an equiatomic ratio, and the metal atomic ratio of Hf to Ta is 1:4, and the mass percentage of Zr in TaZr is 1%.

[0029] The preparation method of the Pd / (TaHfNbZr)C / TaZr composite film of this embodiment comprises the following steps:

[0030] Step 1: Evenly mix tantalum beans and zirconium sponge, and then smelt them in an arc melting furnace to obtain TaZr alloy;

[0031] Step 2: Using a rolling process, the TaZr alloy obtained in step 1 is processed into a TaZr foil with a thickness of 0.3 mm, and then processed to a target size, polished and bright, and set aside;

[0032] Step 3: using a magnetron sputtering process, a TaHfNbZr film layer with an equiatomic ratio is prepared on the surface of the TaZr foil to be used in step 2, and then carbonizing to form a (TaHfNbZr)C film layer to obtain a (TaHfNbZr)C / TaZr composite film; the process for carbonizing to form the (TaHfNbZr)C film layer is as follows: the carbonization gas is a mixed gas of argon and methane, and the volume proportion of methane in the mixed gas is 15%, the carbonization power is 300W, and the time is 30min;

[0033] Step 4: using a magnetron sputtering process, depositing Pd nanoparticles on the surface of the (TaHfNbZr)C / TaZr composite film obtained in step 3, the deposition time is 10 min, and obtaining a (TaHfNbZr)C / TaZr composite film loaded with Pd nanoparticles;

[0034] Step 5: anneal the (TaHfNbZr)C / TaZr composite film loaded with Pd nanoparticles obtained in step 4 under the protection of a mixed atmosphere of argon and hydrogen, with an argon flow rate of 0.15 m 3 / h, the flow ratio of argon to hydrogen is 3:1, the annealing temperature is 500℃±10℃, and a Pd / (TaHfNbZr)C / TaZr composite film is obtained.

[0035] Example 2

[0036] In the Pd / (TiHfNbZr)C / TaZr composite film of this embodiment, Pd is loaded on the surface of the (TiHfNbZr)C / TaZr composite film in the form of nanoparticles, wherein the size of the Pd nanoparticles is 15nm~50nm, (TiHfNbZr)C is obtained by carbonization of a high entropy film mixed with HfNb, Ti and Zr, and has a thickness of 0.15μm. The metal elements of HfNb are in an equiatomic ratio, Ti and Zr are in an equiatomic ratio, and the metal atomic ratio of Hf to Zr is 1:4, and the mass percentage of Zr in TaZr is 3%.

[0037] The preparation method of the Pd / (TiHfNbZr)C / TaZr composite film of the present embodiment comprises the following steps:

[0038] Step 1: Evenly mix tantalum beans and zirconium sponge, and then smelt them in an arc melting furnace to obtain TaZr alloy;

[0039] Step 2: Using a rolling process, the TaZr alloy obtained in step 1 is processed into a TaZr foil with a thickness of 1.0 mm, and then processed to a target size, polished and bright, and set aside;

[0040] Step 3: Using a magnetron sputtering process, a TiHfNbZr film layer with an equiatomic ratio is prepared on the surface of the TaZr foil to be used in step 2, and then carbonizing to form a (TiHfNbZr)C film layer to obtain a (TiHfNbZr)C / TaZr composite film; the process for carbonizing to form the (TiHfNbZr)C film layer is as follows: the carbonization gas is a mixed gas of argon and methane, and the volume proportion of methane in the mixed gas is 40%, the carbonization power is 150W, and the time is 50min;

[0041] Step 4: using a magnetron sputtering process, depositing Pd nanoparticles on the surface of the (TiHfNbZr)C / TaZr composite film obtained in step 3, the deposition time is 20 min, and obtaining a TiHfNbZr)C / TaZr composite film loaded with Pd nanoparticles;

[0042] Step 5: The (TiHfNbZr)C / TaZr composite film loaded with Pd nanoparticles obtained in step 4 is annealed under the protection of a mixed atmosphere of argon and hydrogen, with an argon flow rate of 0.4 m 3 / h, the flow ratio of argon to hydrogen is 1:1, the annealing temperature is 500℃±10℃, and a Pd / (TiHfNbZr)C / TaZr composite film is obtained.

[0043] Example 3

[0044] In the Pd / (HfNbZr)C / TaZr composite film of this embodiment, Pd is loaded on the surface of the (HfNbZr)C / TaZr composite film in the form of nanoparticles, wherein the size of the Pd nanoparticles is 25nm~50nm, (HfNbZr)C is obtained by carbonization of a high entropy film mixed with HfNb and Zr, and has a thickness of 0.1μm. The metal elements of HfNb are in an equiatomic ratio, and the metal atomic ratio of Hf to Zr is 4:1, and the mass percentage of Zr in TaZr is 8%.

[0045] The preparation method of the Pd / (HfNbZr)C / TaZr composite film of this embodiment comprises the following steps:

[0046] Step 1: Evenly mix tantalum beans and zirconium sponge, and then smelt them in an arc melting furnace to obtain TaZr alloy;

[0047] Step 2: Using a rolling process, the TaZr alloy obtained in step 1 is processed into a TaZr foil with a thickness of 0.6 mm, and then processed to a target size, polished and bright, and set aside;

[0048] Step 3: Using a magnetron sputtering process, a HfNbZr film layer with an equiatomic ratio is prepared on the surface of the TaZr foil to be used in step 2, and then carbonizing to form a (HfNbZr)C film layer to obtain a (HfNbZr)C / TaZr composite film; the process for carbonizing to form the (HfNbZr)C film layer is as follows: the carbonization gas is a mixed gas of argon and methane, and the volume proportion of methane in the mixed gas is 30%, the carbonization power is 260W, and the time is 40min;

[0049] Step 4: using a magnetron sputtering process, depositing Pd nanoparticles on the surface of the (HfNbZr)C / TaZr composite film obtained in step 3, the deposition time is 15 min, and obtaining a (HfNbZr)C / TaZr composite film loaded with Pd nanoparticles;

[0050] Step 5: anneal the (HfNbZr)C / TaZr composite film loaded with Pd nanoparticles obtained in step 4 under the protection of a mixed atmosphere of argon and hydrogen, with an argon flow rate of 0.3 m 3 / h, the flow ratio of argon to hydrogen is 2:1, the annealing temperature is 500℃±10℃, and a Pd / (HfNbZr)C / TaZr composite film is obtained.

[0051] Example 4

[0052] In the Pd / (HfNbTiTaZr)C / TaZr composite film of this embodiment, Pd is loaded on the surface of the (HfNbTiTaZr)C / TaZr composite film in the form of nanoparticles, wherein the size of the Pd nanoparticles is 25nm~50nm, (HfNbTiTaZr)C is obtained by carbonization of a high entropy film mixed with HfNb, Ti, Ta, and Zr, and has a thickness of 0.1μm. The metal elements of HfNb are in an equiatomic ratio, Ti, Ta, and Zr are in a metal equiatomic ratio, and the metal atomic ratio of Hf to Ta is 1:1, and the mass percentage of Zr in TaZr is 0.5%.

[0053] The preparation method of the Pd / (HfNbTiTaZr)C / TaZr composite film of the present embodiment comprises the following steps:

[0054] Step 1: Evenly mix tantalum beans and zirconium sponge, and then smelt them in an arc melting furnace to obtain TaZr alloy;

[0055] Step 2: Using a rolling process, the TaZr alloy obtained in step 1 is processed into a TaZr foil with a thickness of 0.6 mm, and then processed to a target size, polished and bright, and set aside;

[0056] Step 3: Using a magnetron sputtering process, a HfNbTiTaZr film layer with an equiatomic ratio is prepared on the surface of the TaZr foil to be used in step 2, and then carbonizing to form a (HfNbTiTaZr)C film layer to obtain a (HfNbTiTaZr)C / TaZr composite film; the process for carbonizing to form the (HfNbTiTaZr)C film layer is as follows: the carbonization gas is a mixed gas of argon and methane, and the volume ratio of methane in the mixed gas is 30%, the carbonization power is 260W, and the time is 40min;

[0057] Step 4: Using a magnetron sputtering process, Pd nanoparticles are deposited on the surface of the (HfNbTiTaZr)C / TaZr composite film obtained in step 3 for 15 min to obtain a (HfNbTiTaZr)C / TaZr composite film loaded with Pd nanoparticles;

[0058] Step 5: anneal the (HfNbTiTaZr)C / TaZr composite film loaded with Pd nanoparticles obtained in step 4 under the protection of a mixed atmosphere of argon and hydrogen, with an argon flow rate of 0.3 m 3 / h, the flow ratio of argon to hydrogen is 2:1, the annealing temperature is 500℃±10℃, and a Pd / (HfNbTiTaZr)C / TaZr composite film is obtained.

[0059] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A Pd / (HfNb system)C / TaZr composite film, characterized in that: Pd is loaded on the surface of the (HfNb-based) C / TaZr composite film in the form of nanoparticles, wherein the size of the Pd nanoparticles is 5nm to 50nm, and the (HfNb-based) C is obtained by carbonizing a high entropy film mixed with HfNb and one or more of Ti, Ta, and Zr, with a thickness of 0.05μm to 0.15μm, and the mass percentage of Zr in TaZr is 0.5% to 8%.

2. A Pd / (HfNb system)C / TaZr composite film according to claim 1, characterized in that: The metal elements of HfNb in the (HfNb-based)C are in an equiatomic ratio, and the (HfNb-based)C is obtained by carbonizing a high entropy film mixed with HfNb and one or more of Ti, Ta, and Zr, wherein the metal atomic ratio of Hf to any one of Ti, Ta, and Zr is 1:4 to 4:

1.

3. A Pd / (HfNb system)C / TaZr composite film according to claim 1, characterized in that: The mass percentage of Zr in the TaZr is 0.5% to 3%.

4. A method for preparing a Pd / (HfNb-based)C / TaZr composite film as claimed in any one of claims 1 to 3, characterized in that: The method comprises the following steps: Step 1: Evenly mix tantalum beans and zirconium sponge, and then smelt them in an arc melting furnace to obtain TaZr alloy; Step 2: Using a rolling process, the TaZr alloy obtained in step 1 is processed into a TaZr foil, which is then processed to a target size and polished for standby use; Step 3: using a magnetron sputtering process, a HfNb film layer is prepared on the surface of the TaZr foil to be used in step 2, and then carbonized to form a (HfNb) C film layer to obtain a (HfNb) C / TaZr composite film; Step 4: using a magnetron sputtering process, depositing Pd nanoparticles on the surface of the (HfNb-based) C / TaZr composite film obtained in step 3 to obtain a (HfNb-based) C / TaZr composite film loaded with Pd nanoparticles; Step 5: annealing the (HfNb-based) C / TaZr composite film loaded with Pd nanoparticles obtained in step 4 under the protection of a mixed atmosphere of argon and hydrogen to obtain a Pd / (HfNb-based) C / TaZr composite film.

5. The preparation method according to claim 4, characterized in that: The thickness of the TaZr foil in step 2 is 0.1 mm to 0.3 mm.

6. The preparation method according to claim 4, characterized in that: The process of carbonizing the (HfNb-based) C film layer in step three is as follows: the carbonization gas is a mixture of argon and methane, and the volume proportion of methane in the mixture is 15% to 40%, the carbonization power is 150W to 300W, and the time is 30min to 50min.

7. The preparation method according to claim 4, characterized in that: The time for depositing Pd nanoparticles in step 4 is 10 min to 20 min.

8. The preparation method according to claim 4, characterized in that: The argon flow rate in the argon and hydrogen mixed atmosphere in step 5 is 0.15m 3 / h~0.4m 3 / h, the flow ratio of argon to hydrogen is 3:1 to 1:

1.

9. The preparation method according to claim 4, characterized in that: The temperature of the annealing treatment in step 5 is 500°C±10°C.

Citation Information

Patent Citations

  • Method of making a composite metal gas separation membrane

    CN103998119A

  • A method of making a hydrogen separation composite membrane

    CN104010713A

  • Preparation process of high-hydrogen-permeability isotope and high-temperature-resistant TaVNbZr / (TaVNbZrM) Nx gradient barrier layer

    CN115029677A

  • Preparation process of high-temperature-resistant TaVNb / TaVNbHfZr composite gradient barrier layer for tantalum / palladium catalytic hydrogen purification

    CN115074685A

  • Vanadium alloy membrane material for ammonia decomposition hydrogen separation and purification and preparation method of vanadium alloy membrane material

    CN115652160A